Deutschvermittlung im Rahmen der Mehrsprachigkeit: ein didaktischer Vorschlag für die Sekundarstufe - Hepp, Marianne (Kritik. Rivista di letteratura e critica culturale, 2023)
Mastering more than one language is becoming more and more the rule rather than the exception in our increasingly plurilingual society. In institutional learning contexts most pupils already master at least another foreign language before they start learning German L3. As suggested by the European Framework of Reference, institutions offering language learning must respond to this situation. The article presents strategies to support learners’ language awareness in the acquisition of German L3 by incorporating their existing L2 language knowledge. A special focus is placed on tertiary language teaching with the sequence German after English (GaE). An example of parallel texts (from the online encyclopedia Wikipedia) is used to show how competences, like reading comprehension, in German as a further foreign language can be built upon the previous language learning experience of English L2.